Understanding the obstacles to successful strategic management implementation in Ecuadorian SMEs - Gelmar Garcia-Vidal; Alexander Sanchez-Rodriguez; Reyner Perez-Campdesuner; Rodobaldo Martinez-Vivar; Laritza Guzman-Vilar (Problems and Perspectives in Management, 2024)
Despite full recognition of strategic management in the success of small and medium-sized enterprises (SMEs), little attention has been paid to the factors that contribute to the failure of its implementation in the Ecuadorian context. Therefore, the purpose of this study is to investigate the obstacles that hinder the successful implementation of strategic management in SMEs in Ecuador. A quantitative study approach was employed. The initial sample comprised 105 entrepreneurs, who were administered a checklist to evaluate the status of strategic planning implementation within their organizations. Based on their responses, nine entrepreneurs were selected for in-depth analysis, categorized as follows: three entrepreneurs with a high level of strategic management implementation, three with a moderate level of implementation, and three with minimal or no strategic management practices. This identified the primary obstacles to effective strategic management implementation. Finally, a comprehensive survey was applied to all participants to quantify these barriers, which allowed the construction of the final model used for the subsequent analysis. Through structural equation modeling, the study demonstrated that these obstacles negatively and significantly correlated with the level of strategic management implementation, revealing that businesses with minimal or no implementation experienced significantly different sales performance compared to those with higher levels of strategic management practices.